2012
DOI: 10.1021/jp300585d
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Serum Albumin Bioconjugated Gold Nanoparticles: Synthesis, Hemolysis, and Cytotoxicity toward Cancer Cell Lines

Abstract: Bovine serum albumin (BSA) conjugated gold (Au) nanoparticles (NPs) were synthesized to explore their applications as drug delivery vehicles in systemic circulation. They showed little hemolysis and cytotoxic responses essentially required for such applications. This study shows some of the important physiochemical aspects needed for an appropriate synthesis of BSA-conjugated NPs where unfolded BSA is an essential reaction component. Unfolding of BSA was carried out under different experimental conditions in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
138
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(145 citation statements)
references
References 67 publications
(34 reference statements)
7
138
0
Order By: Relevance
“…To facilitate bioconjugation and improve the biocompatility, the AuNRs are conjugated with BSA using a previously described method [54,58,59]. Figure 2b shows that BSA modification results in a small red-shift and broadening of the LSPR peak as shown in Figure To compare the size effect on the performance of AuNRs in the subsequent cytotoxity and cell uptake studies, 14 nm diameter bAuNRs are also synthesized by the common seed-mediated method as the control.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…To facilitate bioconjugation and improve the biocompatility, the AuNRs are conjugated with BSA using a previously described method [54,58,59]. Figure 2b shows that BSA modification results in a small red-shift and broadening of the LSPR peak as shown in Figure To compare the size effect on the performance of AuNRs in the subsequent cytotoxity and cell uptake studies, 14 nm diameter bAuNRs are also synthesized by the common seed-mediated method as the control.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…[1][2][3][4][5] The characteristics of each stabilizer have a signicant impact on the shape, size, aggregation, and the size distribution of the synthesized materials. [6][7][8][9][10] For the synthesis of AgNPs, environmentally benign biodegradable non toxic natural polymers, especially polysaccharide, have an edge over other stabilizers due to the weak interactions with the nanoparticles. [11][12][13] Raveendran et al in their pioneering work suggested that the polysaccharides containing large numbers of -OH groups, formed inter and intra chain hydrogen bonds and acted as a template for nanoparticle growth.…”
Section: Introductionmentioning
confidence: 99%
“…On careful observation of Fig. 2(a), it can be seen that in concomitant with quenching, slight blue shift (∼8 nm) is observed, which itself suggest the unfolding or change in the conformation of xanthine oxidase and shifting of its hydrophobic residues (Tyr/Trp) to a non polar environment [53,54]. It is to note over here, that shoulder peak is not intense due to devoid of exact excitation wavelength (280 nm) encompassing mainly tyrosine residues.…”
Section: Intrinsic Fluorescence Quenching and Binding Interactionsmentioning
confidence: 97%